2020
DOI: 10.1016/j.jinf.2020.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the excess risk of mortality in the first wave of COVID-19: Cross sectional study of the English sentinel network

Abstract: Objectives: Few studies report contributors to the excess mortality in England during the first wave of coronavirus disease 2019 (COVID-19) infection. We report the absolute excess risk (AER) of mortality and excess mortality rate (EMR) from a nationally representative COVID-19 sentinel surveillance network including known COVID-19 risk factors in people aged 45 years and above. Methods: Pseudonymised, coded clinical data were uploaded from contributing primary care providers (N = 1,970,314, ≥45years). We calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
(45 reference statements)
2
43
0
1
Order By: Relevance
“…Given the limited data on COVID-19 and related risk factors, 3 5 , 17 this finding is entirely novel and not easily explained. It may be a chance statistical finding due to multiple hypothesis testing and future studies should look to confirm the relationship observed in these data.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given the limited data on COVID-19 and related risk factors, 3 5 , 17 this finding is entirely novel and not easily explained. It may be a chance statistical finding due to multiple hypothesis testing and future studies should look to confirm the relationship observed in these data.…”
Section: Discussionmentioning
confidence: 83%
“… 13 Establishing whether this is also the case for hypertensive patients living in the community is important because the focus on routine chronic disease management has reduced during the pandemic. 14 Based on previous studies, 3 5 , 13 , 15 17 we hypothesized that uncontrolled blood pressure would be associated with worse COVID-19 outcomes for hypertensive patients with suspected COVID-19. We used the electronic health records from primary care to test this hypothesis and examined the association between blood pressure control and SARS-CoV-2 infection, COVID-19–related hospitalization, and death.…”
mentioning
confidence: 99%
“…The collateral damage due to co-infection of COVID-19 with other respiratory pathogens and collateral benefits due to the implementation of COVID-19 preventative measures has been recently reported in the studies [ 3 , 4 ].…”
mentioning
confidence: 99%
“…We read with interest the study by de Lusignan et al, who found that, among 1,970,314 UK primary care patients aged ≥ 45 years, being male, increasing age, chronic disease, Black ethnicity and deprivation were associated with excess mortality during the first wave of the COVID-19 pandemic 1 . These findings highlight the unequal burden of COVID-19 across society and reflect our patient and staff experience at North Middlesex University Hospital (NMUH) 2 .…”
mentioning
confidence: 99%